Muhammad Ali - Skinner, J. E. (Sports unite us., 2019)
Explores how Muhammad Ali inspired others through his activism, highlighting his career and the causes he felt strongly about. Includes a timeline, text-related questions, resources for further information, a glossary, and color photographs.